Alone in Paradise: A Review of the Literature Related to Single, Immigrant Mothers in Canada - Lam, Gia; Collins, Sandra; Wong, Gina (Journal of the Motherhood Initiative for Research and Community Involvement, 2020)
In most studies, the phenomena of immigration and single motherhood are examined and explored in isolation from each other. In this manuscript, we adopted intersectionality theory as the framework for examining the literature related to the lived experiences of single, immigrant mothers in Canada. We explored single motherhood and immigration in relation to multiple points of intersection concerning dimensions of cultural identity. We began by examining how intersections of gender and ethnicity affect single, immigrant mothers in terms of self-perception, sociocultural experiences, and acculturation processes. Single, immigrant mothers receive specific gendered messages from their families, cultures of origin, and Canadian culture. These messages, specific to the context of mothering, shape their cultural identity and role in society. We also examined the impact of Canadian and country of origin mothering ideologies on single, immigrant mothers, how discourses around these ideologies endorse potentially unrealistic images of the ideal or good mother, and how they affect the mother-child relationship. Single, immigrant mothers hold multiple, nondominant intersecting identities and may not portray adherence to the dominant mothering ideologies, from either Canada or their country of origin. As a result, they are more vulnerable to marginalization, discrimination, and mental health problems. We considered how the intersections of gender, ethnicity, single motherhood, social class, and immigration affected single, immigrant mothers’ labour market participation, social support, mental health, and acculturation. We offer insights into the challenges that single, immigrant mothers face and point to ways to improve social and mental health services for these women.